Analysis of Factors Influencing Gen Z's Interest in Using Digital Financial Applications - Nur Afifah Damayanti; Isbandriyati Mutmainah; Dewi Fitriyanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the influence of digital financial literacy, perceived benefits, ease of switching, and perceived risk capability in moderating these variables on Gen Z's interest in using e-wallets. This is a quantitative study. The population in this study is Gen Z in the Greater Jakarta area (Jabodetabek) who use e-wallets. The sampling technique used in this research is convenience sampling. The sample size used in this study is 235 respondents. The data analysis employed is multiple linear regression analysis using SPSS 25 software. The results of this study indicate that digital financial literacy, perceived benefits, and ease of switching have a significant partial effect on Gen Z's interest in using e-wallets, and perceived risk is capable of moderating the influence of digital financial literacy on Gen Z's interest in using e-wallets. Keywords: digital financial literacy, perceived benefits, ease of switching, perceived risk, interest in using